(untitled) (Journal of Architectural Design, 2023)
Serving foreign guests and tourists in restaurants, cafes and bars has its own characteristics, which are associated not so much with some special culture of service (the culture of service should always be high!), but with the food traditions of different peoples. This, by the way, determines the level of culture and the class of the enterprise